ARV-771 Acts as an Inducer of Cell Cycle Arrest and Apoptosis to Suppress Hepatocellular Carcinoma Progression - Deng, Yuanfei; Yu, Cuifu; Chen, Lushi; Zhang, Xin; Lei, Qiucheng; Liu, Qing; Cai, Gengxi; Liu, Fang (Frontiers in Pharmacology, 2022)
Hepatocellular carcinoma (HCC) is the most commonly diagnosed liver cancer with limited treatment options and extremely poor prognosis worldwide. Recently, the proteolysis targeting chimeras (PROTACs), which aim to induce proteasome-mediated degradation of interesting proteins via recruiting E3 ligases, have become the advanced tools and attractive molecules for cancer treatment. However, the anticancer effects of PROTACs in HCC remain to be clarified. Here, we evaluate the anticancer activity of ARV-771, a previously reported PROTAC compound designed for bromodomain and extra-terminal domain (BET) proteins, in HCC. We show that ARV-771 suppresses the cell viability and colony formation of HCC cells via arresting cell cycle progression and triggering apoptosis. Further investigations reveal that ARV-771 notably downregulates multiple non-proteasomal deubiquitinases which are critical to the development of cancers. Additionally, HCC cells can decrease their sensitivity to ARV-771 via activating the MEK/ERK and p38 MAPKs. ARV-771 also inhibits HCC progression in vivo. Moreover, we show that ARV-771 and sorafenib, a Raf inhibitor that clinically used for targeted therapy of liver cancer, can synergistically inhibit the growth of HCC cells. Overall, this study not only explores the anticancer activity of ARV-771 and its underlying mechanisms in HCC, but also deepens our understanding of deubiquitinases, MAPKs, cell cycle, and apoptosis induction in cancer therapy.